ANALISIS POTENSI STASIUN BUMI SATELIT LAPAN-TUBSAT KOTOTABANG UNTUK PENGAWASAN JALUR STRATEGIS SELAT MALAKA (THE POTENTIAL ANALYSIS OF LAPAN-TUBSAT SATELLITE GROUND STATION (KOTOTABANG) FOR OBSERVING THE STRATEGIC CHANNEL OF MALACCA STRAIT) - Chusnul Tri Judianto (Jurnal Teknologi Dirgantara, 2012)
LAPAN-TUBSAT is the first generation of LAPAN satellite program which is developed by technology collaboration between LAPAN and TU Berlin, German. As a surveillance satellite, LAPAN-TUBSAT has ability to observe the earth surface until 5 meter ground resolution by using analog video camera. Utilization of this satellite to observe the strategic location entire Indonesia in real time has not been done thoroughly. Therefore the technical upgrading of the Ground Station in strategic areas such as border areas, the National/International cruise line and National vital objects should be improved. One of the strategic areas of Indonesia is the region of Malacca Strait which is the area of International shipping waterway and border of 4 countries; Indonesia, Malaysia, Singapura and Thailand. Until now, to observe the Malacca region was performed using Rancabungur/Rumpin ground station that have minimum coverage area. The Kototabang ground station is one of the strategic ground stations that cover the entire of Malacca regions which needs to be improved in maintenance and technical operation level. The potential value of Kototabang ground station will be elaborated technically in this paper. Keywords: Kototabang ground station, LAPAN-TUBSAT